Mapping the undergraduate dermatology curriculum: a useful tool towards implementation of national recommendations. (27th November 2019) - Sharma, M.; Scorer, M.; Kent, D.; Murphy, R.; Doody, G.
Summary: Background: Despite the high prevalence of skin complaints in primary care and secondary care, dermatology undergraduate (UG) education remains inconsistent across medical schools. The British Association of Dermatologists (BAD) published a revised national UG curriculum in 2016 to guide UK medical schools on the minimum competencies required in dermatology. Aim: The aim of the study was to determine the alignment of the BAD UG curriculum with the dermatology curriculum of the University of Nottingham School of Medicine. Methods: A curriculum mapping study was undertaken with the development of an electronic searchable database tool to map key areas. Results: Of the 70 intended learning outcomes (ILOs) for dermatology in the medical school, 55 (79%) were mapped to the BAD curriculum, while 14 (20%) required modifications to align them with the BAD ILOs. Two BAD ILOs were unspecified in the current curriculum, and one was deemed redundant. Conclusion: Curriculum mapping is a useful tool to standardize local dermatology ILOs to national recommendations and provides transparency to stakeholders for implementation of the dermatology curriculum.